STUDENTS' GEOMETRY THINKING ON CIRCLE MATERIAL BASED ON VAN HIELE'S THEORY - Rayinda Aseti Prafianti; Novitasari Novitasari; Dian Novi Ambarwati (MATEMATIKA DAN PEMBELAJARAN, 2022)
The purpose of this study was to describe students' geometric thinking skills on circle material based on Van Hiele's theory (Visualization, Analysis, Informal Deduction, Deduction, Rigor). The subjects of this study were 3 students of class IX-A SMP Hang Tuah 4 Surabaya based on their initial mathematical abilities (high, medium, and low). The initial mathematical ability data was obtained from data on report cards for the even semester of the 2021-2022 academic year and based on the considerations of the mathematics teacher for class IX-A. This type of research is descriptive qualitative research. Collecting data in this study used tests and interviews. The test instrument used in this study was a circular geometry test in the form of mathematical questions with circle material arranged based on the Van Hiele indicator without stage 4 (Rigor) with the consideration that the research was conducted in class IX SMP so students have not been able to understand the material at stage 4 (rigor). Student with high initial mathematical abilities, geometric thinking abilities is already at stage 2 (informal deduction). Student with medium mathematical abilities, geometric thinking skills is at stage 2 (informal deduction). Student with low mathematical abilities, geometric thinking skills is at stage 0 (visualization).